PENGARUH PANDEMI COVID-19 TERHADAP ANGKA PERKAWINAN: (Studi Kasus di Kecamatan Lambu Kabupaten Bima) - Rahayu, Putri (Universitas Darunnajah Jakarta, Indonesia, 2022)
Marriage is mandatory for men and women who have desire and ability to perform it. However, this became a prohibition when a marriage has implemented in the era of the Covid-19 pandemic, particularly in the Bima area. This article aims to find out how the covid-19 pandemic affects the marriage rate in the Lambu District Religious Affairs Office by using the sociological approach of law by Soerjono Soekanto, namely looking at the relationship between society and the law related to the implementation of marriage during the pandemic. The results of the research obtained are about the regulation from the Indonesian Ministry of Religion that marriages are limited during the Covid-19 pandemic to avoid transmission through physical contact as well as posponment from potential mate themselves, so that this is the cause of the decline in marriage rates in Bima, Lambu District.